Commercialization of Renewable Energy Technologies : A study of Socio-economic, Technical and Regulatory factors in Finland and Pakistan - Shakeel, Shah Rukh (Vaasan yliopisto, 2019)
Commercialization plays an important role in technologies’ success and failure. The successful transformation of an idea into a product or service is a complex and multifarious process. Commercialization deals with bringing science and technology competencies from the laboratory to market acceptance and use. It ensures that technologies not only meet performance and reliability requirements, but also addresses market needs. Commercialization of renewable energy technologies (RETs) becomes important as there are a number of additional barriers that RETs must surpass to become widely adopted. Success often depends on a number of actors operating at various levels, including government, local bodies, investors, entrepreneurs, society and other stakeholders involved in the process. The literature is replete with evidence indicating the enormous potential of energy generation from renewables. However, their actual contribution to the world’s primary energy supplies remains limited. There is widespread consensus that the low penetration of some renewable energy technologies is no longer because of their technical potential but their commercialization. The objective of this study is to explore how renewable energy technologies can be effectively commercialized. This doctoral dissertation examines cases from Finland and Pakistan to study factors influencing commercialization and causing hindrances to widespread diffusion. This study particularly explores the effect of socio-economic landscape, effect of energy policies, university–industry collaboration, the role of venture capital and factors influencing adoption and establishment of RETs’ market. By employing a mixed methods approach, the findings of this dissertation highlight the role of supportive energy policies, the need to develop a coherent approach, strengthening collaboration between stakeholders, and increase the level of environmental awareness. Based on the findings, this dissertation presents frameworks and mechanisms necessary to address some of these barriers to foster the process of commercialization.

Kaupallistamisella on tärkeä rooli uuden tekniikan liiketoiminnan käynnistymisessä. Idean onnistunut kehittäminen tuotteeksi tai palveluksi voi olla vaativa ja monitahoinen prosessi. Kaupallistaminen liittyy tiede- ja teknologiaosaamisen tuomiseen laboratoriosta aina markkinoille hyväksymiseen ja käyttöön saakka. Se varmistaa, että tekniikat eivät vain täytä suorituskyky- ja luotettavuusvaatimuksia, vaan myös vastaavat markkinoiden tarpeisiin. Uusiutuvien energialähteiden tekniikoiden (RET) kaupallistaminen tulee tärkeäksi, koska RET:ien on ylitettävä lukuisia esteitä, jotta niitä voitaisiin soveltaa laajasti. Menestys riippuu usein useista eri tasojen toimijoista, mukaan lukien valtiovalta, paikalliset toimijat, sijoittajat, yrittäjät, yhteiskunta ja muut prosessissa mukana olevat sidosryhmät. Kirjallisuus on täynnä todisteita, jotka osoittavat uusiutuvien energialähteiden energiantuotannon valtavan potentiaalin. Niiden tosiasiallinen vaikutus maailman primaarienergian hankintoihin on kuitenkin edelleen rajallinen. On laajaa yksimielisyyttä siitä, että joidenkin uusiutuvien energialähteiden tekniikoiden alhainen levinneisyys ei johdu enää niiden teknisistä mahdollisuuksista, vaan niiden kaupallisuudesta. Tämän työn tavoitteena on tutkia, miten uusiutuvan energian tekniikoita voidaan tehokkaasti kaupallistaa. Tässä väitöskirjassa tutkitaan Suomen ja Pakistanin tapaustutkimusten avulla tekijöitä, jotka vaikuttavat kaupallistamiseen ja ovat esteitä laajaan leviämiseen. Tässä työssä tutkitaan erityisesti sosioekonomisten asioiden, energiapolitiikan, yliopistojen ja teollisuuden yhteistyön ja riskipääoman merkitystä RET-markkinoiden perustamiseen. Sovellettaessa kvalitatiivisen ja kvantitatiivisen menettelemän yhdistelmää, tämän tutkielman tulokset korostavat tukevan energiapolitiikan merkitystä, johdonmukaisen lähestymistavan kehittämisen tarvetta, sidosryhmien välisen yhteistyön vahvistamista ja ympäristötietoisuuden lisäämistä. Tulosten perusteella tämä väitöskirja tarjoaa kehykset ja mekanismit, joita tarvitaan esteiden poistamiseen kaupallistamisprosessin tieltä.
Uusiutuvien energiateknologioiden kaupallistaminen : Tutkimus sosioekonomisista, teknisistä ja sääntelytekijöistä Suomessa ja Pakistanissa
Keywords: commercialization; renewable energy technologies; energy policy; roadmap; university–industry collaboration; venture capital; theory of planned behaviour; energia; energiapolitiikka; teknologinen kehitys; energiavarat; kehitystutkimus; fi=Tuotantotalous|en=Industrial Management|